Konsep Skopos dan aspek fungsionalnya dalam penerjemahan - Masduki, Masduki (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2011)
It is often said that Skopos theory has abolished the position of the source text. Nevertheless, translators still have to translate source texts, and to do this, they must identify translation units and decide what to do with them in the translation process. The same applies to translation description and criticism or even quality assessment. In order to compare source and target texts and achieve a fair judgment of a translation, translators need the communicative function of the translation unit. This article deals with the basic concept of Skopos and the functional aspects that come into play both in translation and translation description.